The Analysis of the Legal Relationship Between Participants of Specialist Doctor Education Programs (PPDS) and Teaching Hospitals in Labor Law - Okky Ocktavianti; Bachrul Amiq; Hikam Muzakky (NOVUM : JURNAL HUKUM, 2024)
The implementation of specialized medical education involves two main aspects: academic training and healthcare services at Teaching Hospitals. While Postgraduate Medical Students (PPDS) fall under the authority of educational institutions, they also serve roles in hospitals, creating the need for clearer legal regulation. Unlike the well-defined relationship between educational institutions and teaching hospitals—governed by a Cooperation Agreement under the Medical Education Act—the legal status of PPDS within hospitals remains unregulated. This study aims to identify the legal basis for PPDS involvement in healthcare services and assess whether such involvement constitutes an employment relationship under labor law. Using a juridical-normative approach, the research finds that, due to the lack of specific legislation, each Teaching Hospital independently regulates the PPDS relationship through internal policies. Labor law defines employment relationships cumulatively, requiring elements such as work, orders, and remuneration. The study concludes that PPDS service in hospitals does not fulfill all these elements—particularly remuneration—since the incentives PPDS receive differ from the legal concept of wages. As a result, the relationship between PPDS and Teaching Hospitals cannot be categorized as an employment relationship under labor law.